Nur Muhammad Concept in Hikayat Nur Muhammad - Iffah Fauziah Rahardy (PIKTORIAL : Journal of Humanities, 2022)
The aim of this research is to produce an edit text litography of Hikayat Nur Muhammad in the framework of philology. Litography text is still rarely use in the philology research. Therefore, the researcher choose this text to be the object of this research. The researcher compare two litography text which is located in British Library and Kebangsaan Malaysia University. There are many litography text, so the method used is method of foundation (legger). The chosen text becomes the most powerful text for the present edition, which is located in Kebangsaan Malaysia University. In the literature reception, the researcher wil reveal the concept of Nur Muhammad  in the simply form. During this time, Hikayat Nur Muhammad always have some general perception, is based on the mysticism concept, so that the general reader can’t understand well. Therefore, in this research, the researcher will reformulate Nur Muhammad easily so that the general reader can understand well. The researcher consider this concept can be understand by three point, that is the creation of human being process, the purpose of creation, and ‘the return’ of human being to the Creator. Allah create the world as macrocosm, which is the human being as microcosm will be lived. In the living of this world, human being have a main duty, is worship to Allah. This worship can be shaped by five aspect, are the confession that there is no God other than Allah and the Prophet Muhammad is his Meddenger, shalat, fasting, obligatory alms, and the pilgrimage to Mecca. After the human being’s duty finished, human being will ‘return’ to Allah and will occupy in ‘last place’, based on his deed.